If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 2f + 2 Reorder the terms: 18 = 2 + 2f Solving 18 = 2 + 2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2f' to each side of the equation. 18 + -2f = 2 + 2f + -2f Combine like terms: 2f + -2f = 0 18 + -2f = 2 + 0 18 + -2f = 2 Add '-18' to each side of the equation. 18 + -18 + -2f = 2 + -18 Combine like terms: 18 + -18 = 0 0 + -2f = 2 + -18 -2f = 2 + -18 Combine like terms: 2 + -18 = -16 -2f = -16 Divide each side by '-2'. f = 8 Simplifying f = 8
| 11x+16=4x-5 | | 7m-4=9(3m+4) | | 6y-4=23-3y | | 6g+4(-7+5g)=1-g | | 7(x-5)=6(x+5) | | -4y+7=35y-6 | | 14x-5=1+11x | | 0=-2a | | y=3 | | 2x-13=-8x+27 | | 4(x-6)+4=6(x+2)-6 | | 2x=7x-15 | | y=3x+5 | | 4y-30= | | 18x-48=6x-12 | | -3(5x-4)=-21 | | 2x+12=5x-9 | | 10x=6x+8 | | 1.5=3x | | 6-2(3x-5)=10 | | 3(x+8)=18 | | 12-(2x+8)=x+16 | | 4x-6=3x | | 4(x-7)=40 | | 8x=5x+4.5 | | .66=3x | | -2x=-3x+8 | | 16p-4=4(2p-3) | | x+5=0 | | 32=12b-4 | | 2x-13=8x+27 | | 6y+5-y= |